Effect of storage temperatures on growth and survival of Escherichia coli O157: H7 inoculated in foods from a neotropical environment - Arias, María Laura; Monge-Rojas, Rafael; Chaves, Carolina; Antillón, Florencia (Revista de Biología Tropical, 2001)
Escherichia coli O157: H7 has emerged as a new pathogen and is found worldwide. We studied the effect of several storage temperatures on the survival of this bacterium in common foods from a neotropical environment (Costa Rica) because at least seven clinical cases have been reported from the country, and no epidemiological link or probable food association has been described. High (106-108 CFU/ml) and low (104-106 CFU/ml) populations of E. coli were inoculated (three replications) in ground meat, chopped cabbage, chicken giblets and pasteurized milk and incubated at 0, 6 and 12ºC for 24, 48 and 72 h. Vegetables and milk were also stored at 22ºC for the same periods. The E. coli O157: H7 enumeration was done according to the methodology described in the Bacteriological Analytical Manual. Populations of E. coli O157: H7 showed either an increasing or decreasing trend, according to temperature, time or food base. Our data indicate that E. coli O157: H7 is capable of surviving and growing in meat, cabbage, milk and chicken giblets; food items commonly consumed by Costa Ricans.